The impact of basketball on the social adjustment of Chinese middle school students: the chain mediating role of interpersonal relationships and self-identity - Haoran, Sui; Tianci, Lu; Hanwen, Chen; Baole, Tao; Yiran, Chen; Yan, Jun (Frontiers in Psychology, 2023)
Background This study examines the effects of 12 weeks of basketball on interpersonal relationships, self-identity and social adjustment of middle school students, as well as exploring the mediating role of interpersonal relationships and self-identity in basketball’s influence on social adjustment. Methods A total of 87 students from a middle school in Jiangsu Province, China, were selected to participate in this study. A 12-week basketball intervention experiment was conducted, and questionnaires were administered to measure the study variables. Common method bias test, normality test, ANOVA and Pearson correlation analysis were used to analyze the study variables. The theoretical model of this study was also validated using the Process plug-in developed by Hayes, setting p < 0.05 (two-tail) as statistically significant. Results After a 12-week basketball intervention experiment, the interpersonal relationships, self-identity and social adjustment of the middle school students in the experimental and control groups showed improvement, with the experimental group showing significantly more significant improvement than the control group. A 12-week basketball intervention can positively impact the social adjustment of middle school students, with interpersonal relationships and self-identity acting as a chain mediator in the impact process.